Relationships of Contextual Supports and Barriers in Choice Behavior for Associate Degree and Diploma Registered Nurses - (:unkn) unknown (My University, 2013)
Currently, the majority of practicing registered nurses (RN) are associate degree in nursing (ADN) or diploma prepared, and the majority of ADN and diploma RNs do not return to school to get a BSN. Yet, there is increasing evidence that the educational level of a RN makes a difference in patient outcomes; having BSN RNs in a facility improves patient outcomes. Very little is known about effective strategies for ADN and diploma RNs to return to school. The Social Cognitive Career Theory (SCCT) contains a choice behavior model that could explain some of the supports or barriers for a RN to return for a BSN. The instrument, BSN Choice Behavior, was used to measure the variables that explain some of the relationships of whether or not a RN will go back to school to get a BSN. Based upon the analysis of 343 ADN and diploma RNs, the results showed that some of the variables within the SCCT did correlate with a RN's intent to return to BSN School. Outcome expectations, efficacy, and contextual supports did result as significant predictors of intent to return to school. Additional research is needed to determine the difference between ADN and diploma RN choice behavior beliefs. However, findings from this study could assist with developing appropriate recruitment and supports for ADN and diploma RNs to return to school for a BSN.
Keywords: ADN RN; Choice Behavior; Contextual Supports and Barriers; Diploma RN; RN-BSN Education; Social Cognitive Career Theory